ANALISIS MODEL THINK PAIR SHARE (TPS) DENGAN MENGGUNAKAN MEDIA KARTU SOAL PADA PEMBELAJARAN IPAS KELAS IV SD INPRES AWAALAH - Safarudin; Muhammad Abdullah; Marzuki Galeko (Jurnal Edukasi, 2026)
This study aims to analyse the effectiveness of the Think Pair Share (TPS) model using question card media in the teaching of Science and Social Studies (IPAS) for fourth-grade students at SD Inpres Awaalah, Alor Barat Laut District, during the 2024/2025 academic year. The TPS model was chosen as it involves individual thinking, paired discussion, and group sharing, which are considered effective in enhancing students active participation and conceptual understanding. The use of question card served as an engaging tool to support interactive learning. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that the application of the TPS model with question card media improved student engagement, reinforced subject comprehension, and encouraged collaboration among students. Teachers also responded positively to this model as it fostered a more collaborative and effective learning environment.